Prey selection and predation behavior of free-roaming domestic cats (Felis catus) in an urban ecosystem: Implications for urban cat management. (April 2022) - Herrera, D.J.; Cove, M.V.; McShea, W.J.; Flockhart, D.T.; Decker, S.; Moore, S.M.; Gallo, T.
Abstract: The ecological impact of free-roaming domestic cats ( Felis catus ) is well-studied. However, despite receiving considerable attention in both the scientific and popular literature, predation behavior is rarely an explicit consideration when developing cat population management plans. We used motion-activated wildlife cameras to document predation events by cats in Washington, D.C. (U.S.A), and assessed the relationships between predation and local environmental characteristics. Our analyses reveal that predation by cats is greatest where supplemental food is most abundant, and that the probability of a cat preying upon a native species increases closer to forest edges. Conversely, we found that the probability of a cat depredating a non-native brown rat increases with increasing distance from forest edges. Therefore, we recommend the implementation of cat exclusionary buffer zones around urban forests and that free-roaming domestic cat management policies explicitly consider the spatial location of cat-feeding sites. Our findings provide a data-driven approach to free-roaming cat management. Highlights: Density of supplemental food is positively correlated with rates of predation by free-roaming domestic cats in urban areas The probability of cat predation of native species decreases with increasing distance from forest edge The probability of cat predation of rats surpasses the probability of native species predation at 250 m from forest edge These findings can inform cat management strategies to reduce impacts on wildlife based on feline predatory behavior